Biophysical controls on light response of net CO2 exchange in a winter wheat field in the North China Plain. - Xiaojuan Tong; Jun Li; Qiang Yu; Zhonghui Lin (PLoS ONE)
To investigate the impacts of biophysical factors on light response of net ecosystem exchange (NEE), CO2 flux was measured using the eddy covariance technique in a winter wheat field in the North China Plain from 2003 to 2006. A rectangular hyperbolic function was used to describe NEE light response. Maximum photosynthetic capacity (P max) was 46.6 ± 4.0 µmol CO2 m(-2) s(-1) and initial light use efficiency (α) 0.059 ± 0.006 µmol µmol(-1) in April-May, two or three times as high as those in March. Stepwise multiple linear regressions showed that P max increased with the increase in leaf area index (LAI), canopy conductance (g c) and air temperature (T a) but declined with increasing vapor pressure deficit (VPD) (P<0.001). The factors influencing P max were sorted as LAI, g c, T a and VPD. α was proportional to ln(LAI), g c, T a and VPD (P<0.001). The effects of LAI, g c and T a on α were larger than that of VPD. When T a>25°C or VPD>1.1-1.3 kPa, NEE residual increased with the increase in T a and VPD (P<0.001), indicating that temperature and water stress occurred. When g c was more than 14 mm s(-1) in March and May and 26 mm s(-1) in April, the NEE residuals decline disappeared, or even turned into an increase in g c (P<0.01), implying shifts from stomatal limitation to non-stomatal limitation on NEE. Although the differences between sunny and cloudy sky conditions were unremarkable for light response parameters, simulated net CO2 uptake under the same radiation intensity averaged 18% higher in cloudy days than in sunny days during the year 2003-2006. It is necessary to include these effects in relevant carbon cycle models to improve our estimation of carbon balance at regional and global scales.